Effect of Solvents on Extraction and Adsorption of Natural Dyes Extracted from Cordyline fruticosa and Hylocereus polyrhizus - A.M. Al-Alwani, Mahmoud; Bakar Mohamad, Abu; Amir H. Kadhum, Abdul; Ludin, N.A. (Asian Journal of Chemistry, 2014)
Different solvents, such as n-hexane, ethanol, acetonitrile, chloroform, ethyl-ether, methanol and water, were used to extract dyes from the leaves of Cordyline fruticosa and the fruits of Hylocereus polyrhizus, to be used as sensitizers for dye-sensitized solar cells. The dyes extracted from these species contained chlorophyll, betanin and betaxanthin. Methanol and water were shown to be the best solvents according to the highest absorbance obtained from the dye solutions of C. fruticosa and H. polyrhizus, respectively. The photochemical performance of dyes extracted from C. fruticosa with different solvents mixed with TiO2 indicated that the main effectual solvent was a mixture of methanol and water, in a ratio of 3:1. Meanwhile, water was demonstrated to be the most effective solvent for the H. polyrhizus dye adsorption on TiO2 particles. This study expects the good absorption efficiency of TiO2 with natural dyes to be used for future applications in dye-sensitized solar cell devices.